The symmetry breaking solutions of the nonlocal Alice–Bob B-type Kadomtsev–Petviashvili system - Peng Dong; Zheng-Yi Ma; Hui-Ling Wu; Quan-Yong Zhu (Results in Physics, 2023)
The (2+1)-dimensional B-type Kadomtsev–Petviashvili equation is an integrable model, which can be used to describe the shallow water wave in a fluid. In this paper, the nonlocal Alice–Bob B-type Kadomtsev–Petviashvili system is induced via the principle of PˆsxPˆsyTˆd symmetry. An extended Bäcklund transformation introduced, the symmetry breaking solution, which contains the soliton, breather, lump and their hybrid structures for this system, is solved through the Hirota bilinear form.